2019
DOI: 10.31227/osf.io/nrmgu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Level of Correlation in the Depth of Groundwater Wells: Iron and Chloride

Abstract: Groundwater quality in each region is not always the same, this influenced by climate factors, lithology, time, human activities. The purpose of the research that conducted was to see the relationship among the depth of groundwater wells in two different study locations on the concentration of iron (Fe) and Chloride (Cl) levels in each sample. This research located in Mattiro Baji Village, Pangkep Regency, South Sulawesi and Sindulang Satu Urban Village, Manado City, North Sulawesi. The research sample amounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A number of studies have been conducted to determine the quality of groundwater as a source of drinking water in several regions in Indonesia (Ibrahim, 2017;Permana et al, 2020;Ronny et al, 2019;Hamzar et al, 2021;Tangahu et al, 2021;Vina et al, 2021). The results of research by analyzing the quality of groundwater at a depth of 2.8 to 4 m based on physical parameters (color, odor, taste, and TDS) concluded that the quality of groundwater at that depth did not meet the requirements for drinking water (Permana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been conducted to determine the quality of groundwater as a source of drinking water in several regions in Indonesia (Ibrahim, 2017;Permana et al, 2020;Ronny et al, 2019;Hamzar et al, 2021;Tangahu et al, 2021;Vina et al, 2021). The results of research by analyzing the quality of groundwater at a depth of 2.8 to 4 m based on physical parameters (color, odor, taste, and TDS) concluded that the quality of groundwater at that depth did not meet the requirements for drinking water (Permana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on laboratory testing, they judged that three of the five samples were unsafe for human consumption because they did not fulfill the requirements for drinking water quality standards set by the Minister of Health of the Republic of Indonesia (Hamzar et al, 2021). A study with 18 groundwater sampling locations in Pangkep Regency, South Sulawesi Province, also shows that the quality of groundwater in each location is not always the same because it is influenced by climatic factors and human activities (Ronny et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dug wells (shallow wells) are one of the most common and widespread constructions of wells used to take groundwater for small communities and individual houses as drinking water with a depth of 7-10 meters from ground level [6], [7]. Dug wells provide water that comes from layers of soil that are relatively close to the surface of the soil and are therefore easily exposed to contamination through seepage.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact on aesthetics is that it can cause dry skin, the economic losses that can arise are decreasing soil fertility of agricultural land [4]. In fulfilling clean water needs, humans usually utilize water sources around the settlements, both natural and after processing first [5].…”
Section: Introductionmentioning
confidence: 99%